Epistemic justice and the integration of local ecological knowledge for marine conservation: Lessons from the Seychelles. (July 2020) - Baker, Susan; Constant, Natasha Louise
Abstract: This article applies the concept of epistemic justice to stakeholder participation in natural resource management, in particular in relation to the marine environment. It explores the dynamics involved in promoting 'epistemic justice' in the governance of public policy for sustainability. This is illustrated using a case study exploring the role of local ecological knowledge of artisanal fishers for marine spatial planning in the Seychelles. Qualitative data was first collected through interviews with key informants and in participatory stakeholder workshops exploring the key threats, trade-offs, and challenges for promoting sustainable futures in the marine environment. Secondly, focus groups with local fishers explored the impacts of marine policy upon access to natural resources and local livelihoods, and detailed the role of local ecological knowledge for supporting marine conservation practice. An analysis of grey literature provided additional, contextual data. The case study demonstrates that local ecological knowledge has an important role in informing fine grained, spatial, and temporal management approaches for marine spatial planning. However, in the absence of trust between state planners and fishing communities', knowledge sharing can be challenging. These factors are exacerbated by restrictions that marine policies place on local livelihoods, and the dominance of western paradigms for conservation that marginalises alternative knowledge contributions. The research points to the importance of promoting epistemic justice practices that bring respectful synthesis in knowledge sharing through addressing issues of credibility, trust, transparency, power inequalities, and accountability of state institutions. Highlights: The concept of epistemic justice theorises the use of LEK in marine conservation policy to cast new light on the multiple dimension of knowledge exclusion, including at both the epistemological and structural levels. Marine conservation initiatives offer avenues for engagement of fisher's knowledge in participatory management of marine resources. Local ecological knowledge provides insights for informing sustainable fishing practices and temporal and spatial systems of management for marine spatial planning. Issues of credibility and trust pose challenges for effective knowledge synthesis. Respectful knowledge synthesis is promoted by developing institutional pathways centred on trust-building, laying the foundations for epistemic justice to prevail.